2007
DOI: 10.1088/0953-2048/20/11/s13
|View full text |Cite
|
Sign up to set email alerts
|

SQUID-based instrumentation for ultralow-field MRI

Abstract: Magnetic resonance imaging at ultra-low fields (ULF MRI) is a promising new imaging method that uses SQUID sensors to measure the spatially encoded precession of pre-polarized nuclear spin populations at a microtesla-range measurement field. In this work, a seven-channel SQUID system designed for simultaneous 3D ULF MRI and magnetoencephalography (MEG) is described. The system includes seven second-order SQUID gradiometers characterized by magnetic field resolutions of 1.2 -2.8 fT/√Hz. It is also equipped with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 25 publications
(42 reference statements)
2
76
0
Order By: Relevance
“…All experimental results, reported in this paper, were obtained using the seven-channel SQUID system for 3D ULF MRI and MEG [23,24], depicted schematically in Fig. 1.…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…All experimental results, reported in this paper, were obtained using the seven-channel SQUID system for 3D ULF MRI and MEG [23,24], depicted schematically in Fig. 1.…”
Section: Instrumentationmentioning
confidence: 99%
“…1. The system includes seven second-order SQUID gradiometers with 37 mm diameter and 60 mm baseline, characterized by magnetic field resolutions of 1.2…2.8 fT/√Hz at 1 kHz [24]. The gradiometers are installed parallel to one another inside a flat-bottom liquid helium cryostat.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultra-low field nuclear magnetic resonance and magnetic resonance imaging (ULF-MR) utilizes a very weak magnetic field, in the order of μT, for its measurement field (B m ) that induces nuclear spin precession [1][2][3][4]. Such a low B m requires (1) a magnetic sensor with a flat frequency response down to as low as 100 Hz or less and (2) a strong prepolarization field (B p ) which magnetizes the sample prior to magnetic resonance measurement to enhance magnetic resonance signal [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much effort has been devoted to design and develop optimized sensors and prototypes relying on superconducting devices. Indeed, recent studies have demonstrated the feasibility of low-field NMR/MRI detection based on Superconducting QUantum Interference Devices (SQUID), relying on a measurement magnetic field ∼ 100 µT combined with a pulsed prepolarizing field ∼ 10 to 100 mT [9,10]. The latter is needed to increase the magnetization of the sample and hence the signal strength.…”
Section: Introductionmentioning
confidence: 99%